Edge profiles in K shell photoabsorption spectra of gaseous hydrides of 3p elements and homologues. (October 2017) - Hauko, R.; Gomilšek, J. Padežnik; Kodre, A.; Arčon, I.; Aquilanti, G.
Abstract: Photoabsorption spectra of gaseous hydrides of 3 p elements (PH3, H2 S, HCl) are measured in the energy region of photoexcitations pertaining to K edge. The analysis of the edge profile is extended to hydrides of 4 p series (GeH4, AsH3, H2 Se, HBr) from an earlier experiment, and to published spectra of 2 p hydrides (CH4, NH3, H2 O, HF) and noble gases Ar, Kr and Ne and SiH4 . The edge profiles are modelled with a linear combination of lorentzian components, describing excitations to individual bound states and to continuum. Transition energies and probabilities are also calculated in the non-relativistic molecular model of the ORCA code, in good agreement with the experiment. Edge profiles in the heavier homologues are closely similar, the symmetry of the molecule governs the transitions to the lowest unoccupied orbitals. In 2 p series the effect of the strong nuclear potential prevails. Transitions to higher, atomic-like levels remain very much the same as in free atoms. Highlights: K -edge absorption profiles of gaseous PH3, H2 S, HCl are measured. Data for 2 p and 4 p homologues are adopted for comparison. Spectral features in 3 p and 4 p series are closely similar, but differ from 2 p series. Experimental data of (2, 3, 4) p hydrides are compared to data of DFT calculations. Transition energies and probabilities are extensively tabulated.